2016
DOI: 10.1021/acsami.6b10597
|View full text |Cite
|
Sign up to set email alerts
|

Novel Li[(CF3SO2)(n-C4F9SO2)N]-Based Polymer Electrolytes for Solid-State Lithium Batteries with Superior Electrochemical Performance

Abstract: Solid polymer electrolytes (SPEs) would be promising candidates for application in high-energy rechargeable lithium (Li) batteries to replace the conventional organic liquid electrolytes, in terms of the enhanced safety and excellent design flexibility. Herein, we first report novel perfluorinated sulfonimide salt-based SPEs, composed of lithium (trifluoromethanesulfonyl)(n-nonafluorobutanesulfonyl)imide (Li[(CFSO)(n-CFSO)N], LiTNFSI) and poly(ethylene oxide) (PEO), which exhibit relatively efficient ionic con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
71
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 97 publications
(72 citation statements)
references
References 51 publications
1
71
0
Order By: Relevance
“…Thus, its practical applications were limited. Clearly, it is extremely urgent to seek some electrolytes with superior safety for the rapid development of Li-ion and/or Li batteries in the next-generation large-scale applications [5,6]. All-solid-state Li-ion batteries are considered to be most promising to address the safety challenges of the current Li-ion batteries, which possess great advantages over the liquid or gel electrolytes, including better safety, non-flammability, non-leakage and excellent design flexibility [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…Thus, its practical applications were limited. Clearly, it is extremely urgent to seek some electrolytes with superior safety for the rapid development of Li-ion and/or Li batteries in the next-generation large-scale applications [5,6]. All-solid-state Li-ion batteries are considered to be most promising to address the safety challenges of the current Li-ion batteries, which possess great advantages over the liquid or gel electrolytes, including better safety, non-flammability, non-leakage and excellent design flexibility [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…DSC analysis evidences the correlation of change in T g with respect to salt concentration. Also, the aromatic nature of Huckel-type anions provides flexibility to PEO matrix which supports faster ion transport as evidenced by an enhancement in ionic conductivity.Ma et al[44] reported the preparation of SPE based on perfluorinated sulfonimide salt-based SPEs, composed of lithium (trifluoromethanesulfonyl) (n-nonafluorobutanesulfonyl)imide (Li[(CF 3 SO 2 )(n-C 4 F 9 SO 2 )-N], LiTNFSI) and poly (ethylene oxide) (PEO) using solution cast technique. The obtained ionic conductivity value was 3.69 × 10 −4 S cm −1 at 90 °C and an anodic electrochemical stability at 4.0 V vs Li + /Li, and sufficient thermal stability (>350 °C).…”
mentioning
confidence: 99%
“…[38][39][40][41][42][43]45,46,48,49 In comparison, the dependence of conductivity on temperature for ceramic electrolytes generally follows a continuous Arrhenius trend. For example, the lithium superionic conductor, Li 10 GeP 2 S 12 , holds an extremely high bulk conductivity of > 10 −2 S cm −1 at 25…”
Section: Future Needs and Prospectsmentioning
confidence: 99%